Survival rural tourism through digital marketing: case study in Kedah – Malaysia and Surabaya – Indonesia - Zulfa, Vivi Rodliyatuz; Yuliawan, Rahmat; Ibrahim, Izura (2023)
Rural tourism, which is distinguished by its cultural diversity and scenic beauty, has long been an important driver of economic growth for rural communities around the world, but various difficulties this industry has encountered recently put its viability in jeopardy. Digital marketing is now a vital instrument for promoting and sustaining rural tourism in the modern day since it has opened up new channels for reaching and interacting with potential tourists. In this study, Kedah, Malaysia, and Surabaya, Indonesia. Two physcally disperate places are use as case studies to evaluate how digital marketing might help rural tourism survive. The study investigates the efficacy of digital marketing tactics used in these areas through a comparative analysis, as well as the degree to which they support the expansion and adaptability of rural tourism in the face of shifting market dynamics. The study uses a mixed methods approach, integrating quantitative information from internet marketing platforms and statistics on visitor arrivals with qualitative interviews with regional tourism authorities, rural business owners, and tourists. The goal of the study is to find effective digital marketing strategies that have benefited rural tourism in Kedah and Surabaya while also revealing any potential obstacles and difficulties that these areas may be facing. According to preliminary findings, digital marketing has helped rural tourism offers in Kedah and Surabaya become more visible and approachable. In order to draw tourists from various markets, it has been crucial to implement social media marketing, search engine optimization, and online booking platforms effectively. The study also identifies differences between the two regions in the efficacy of digital marketing techniques, which are influenced by elements including local infrastructure, internet penetration, and cultural perceptions. The purpose of this study is to add to the body of knowledge on rural tourism and digital marketing by highlighting the unique difficulties and opportunities that Kedah and Surabaya have to deal with. Policymakers, tourism authorities, and rural entrepreneurs in these areas, as well as those in other rural destinations looking to capitalize on the potential of digital marketing to sustain their tourism industries, should take note of the findings. The importance of digital marketing as a crucial tool for the survival and expansion of rural tourism in the modern era is highlighted by this study's findings. Rural destinations may encourage sustainable growth and solidify their position in the global tourism scene by identifying the distinctive qualities of each location and adjusting their digital marketing tactics accordingly.